Synthesis and in vitro evaluation of bone-seeking superparamagnetic iron oxide nanoparticles as contrast agents for imaging bone metabolic activity - Panahifar, A.; Mahmoudi, M.; Doschak, Michael (American Chemical Society, 2013)
In this article, we report the synthesis and in vitro evaluation of a new class of nonionizing bone-targeting contrast agents based on bisphosphonate-conjugated superparamagnetic iron oxide nanoparticles (SPIONs), for use in imaging of bone turnover with magnetic resonance imaging (MRI). Similar to bone-targeting 99mTechnetium medronate, our novel contrast agent uses bisphosphonates to impart bone-seeking properties, but replaces the former radioisotope with nonionizing SPIONs which enables their subsequent detection using MRI. Our reported method is relatively simple, quick and cost-effective and results in BP-SPIONs with a final nanoparticle size of 17 nm under electron microscopy technique (i.e., TEM). In-vitro binding studies of our novel bone tracer have shown selective binding affinity (around 65%) for hydroxyapatite, the principal mineral of bone. Bone-targeting SPIONs offer the potential for use as nonionizing MRI contrast agents capable of imaging dynamic bone turnover, for use in the diagnosis and monitoring of metabolic bone diseases and related bone pathology.